Carbon Intensity Indicator (CII) Calculation Analysis For Operational Feasibility of Passenger Ships - Handi Awaludin Jamil; Benny Cahyono; Nadilah Laksmi Marahaini (International Journal of Science and Environment (IJSE), 2026)
The Maritime industry faces increasing pressure to reduce greenhouse gas emissions under the International Maritime Organization’s Carbon Intensity Indicator (CII) framework. This study evaluates operational performance, fuel consumption, and carbon intensity for two aging passenger ships operated by PT. XYZ (Passenger Ship A, 34 years; Passenger Ship B, 33 years) and assesses whether repowering can improve efficiency and compliance. Financial feasibility is projected using trendline regression under two scenarios: without subsidies and with subsidies. Results indicate that without subsidies, both ships are projected to incur losses from the initial period, with deficits increasing annually. Under subsidies, Passenger Ship A’s gross profit is projected to become negative starting in 2028, while Passenger Ship B is expected to remain financially positive. Environmentally, CII results show rising carbon emission intensity, averaging annual increases of 0.56% for Passenger Ship A and 2.09% for Passenger Ship B, leading to declining CII ratings over time. Passenger Ship A is projected to reach Rating E during 2029–2035, requiring a critical operational decision by 2031, while Passenger Ship B is projected to reach Rating E during 2031–2035, requiring a decision by 2033. Repowering reduces annual fuel consumption by 41.4% and 47.5%, respectively, and improves both ships’ CII ratings to Rating A, supporting continued operation with international environmental compliance.